Developing a hydrological simulation tool to design bioretention in a watershed. (December 2019) - Baek, Sang-Soo; Ligaray, Mayzonee; Park, Jong-Pyo; Shin, Hyun-Suk; Kwon, Yongsung; Brascher, Joseph T.; Cho, Kyung Hwa
Abstract: Continuous urbanization has negatively impacted the ecological and hydrological environments at the global, regional, and local scales. This issue was addressed by developing Low Impact Development (LID) practices to deliver better hydrologic function and improve the environmental, economic, social and cultural outcomes. This study developed a modeling software to simulate and optimize bioretentions among LID in a given watershed. The model calculated a detailed soil infiltration process in bioretention with hydrological conditions (e.g. unsaturated and saturated soil) and hydraulic facilities (e.g. riser and underdrain) and also generated an optimized plan using Flow Duration Curve (FDC). The optimization result from the simulation demonstrated that the location and size of bioretention, as well as the soil texture, are important elements for an efficient bioretention. We hope that this developed software will aid in establishing effective LID strategies for improving urban water sustainability and management. Graphical abstract: Image 1 Highlights: We developed a modeling software to simulate and optimize bioretentions. The model can consider a detailed hydrological and hydraulic mechanism. The location and size of bioretention and soil texture are important for an efficient bioretention. We hope that the model could be useful for appropriate scheme for LID.